Manajemen Mutu Program Studi: Analisis Profil Mutu Lulusan dan Relevansinya dalam Karir Alumni Sejarah Peradaban Islam Tahun 2011 – 2021 - Syafaah, Aah; Nuris, Anwar (UIN SIber Syekh Nurjati Cirebon, 2025)
The analysis of the description of the process of formulating the quality concept of the profile of graduates of the History of Islamic Civilization (SPI) Study Program (SPI) IAIN Syekh Nurjati Cirebon is an integral part of efforts to test the relevance of graduate profiles to graduate careers. This effort was carried out through a survey research method with an exploratory approach to the alumni population from 2011 to 2021 which amounted to 297 people. This approach was chosen based on the assumption that social reality applies typically, subjectively and contextually in space and time, so researchers need to understand it by interpreting the phenomenon in depth in its context. The results of the study show that the mechanism of formulation and preparation is carried out through several stages, namely Need Assessment, Workshop, Formulation and Ratification at the Senate level, Socialization, Improvement. This mechanism produces the formulation of the quality profile of graduates, namely: Historians; Creator of narrative works with the theme of Multimedia-based Islamic Cultural History; Researcher in the field of Islamic Cultural History; Historical Tour Guide; and Cultural Observers. Meanwhile, the level of quality relevance in the career of graduates is relatively low, namely 19% of the object population. This low relevance is caused by several obstacles, namely the lack of job opportunities purely related to the expertise of the History of Islamic Civilization; Linearity of non-educational and educational expertise; Low foreign language and computer/technology (IT) skills; Low socialization and promotion of the SPI Study Program to stakeholders (the world of work).